2021
DOI: 10.1111/cen.14530
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of percutaneous ethanol injection (PEI) in cystic thyroid nodules: A systematic review and meta‐analysis

Abstract: Background Percutaneous ethanol injection (PEI) is used for the treatment of benign cystic thyroid nodules. This systematic review and meta‐analysis aimed to obtain strong evidence of its long‐term efficacy and safety. Methods PubMed, CENTRAL, Scopus and Web of Science databases were searched until November 2020 for studies reporting data on volume reduction rate (VRR), compressive symptoms and cosmetic concerns. Associated complications were assessed. A random‐effects model was designed to pool the data. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The meta-analysis by Cesareo et al ( 56 ) identified no permanent complications in these studies and, reassuringly, the thyroid function was unaffected in all patients. However, early postprocedure complications include mild to moderate pain or local burning sensation, transient dysphonia, vasovagal reaction, and bleeding into the cyst ( 55 ).…”
Section: Nonsurgical Management Of Thyroid Cystsmentioning
confidence: 63%
See 1 more Smart Citation
“…The meta-analysis by Cesareo et al ( 56 ) identified no permanent complications in these studies and, reassuringly, the thyroid function was unaffected in all patients. However, early postprocedure complications include mild to moderate pain or local burning sensation, transient dysphonia, vasovagal reaction, and bleeding into the cyst ( 55 ).…”
Section: Nonsurgical Management Of Thyroid Cystsmentioning
confidence: 63%
“…Four patients (20%) reported mild and transient symptoms (mild pain, a vasovagal reaction, and bleeding into cyst) but none were deemed serious. A recently published systematic review and meta-analysis evaluated a total of 1667 nodules with up to 10 years of follow up ( 56 ). They noted volume reductions of 81% at 12 months, 74% at 5 years, and 69% at 10 years, along with significant reductions in compressive symptoms and cosmetic concerns.…”
Section: Nonsurgical Management Of Thyroid Cystsmentioning
confidence: 99%
“…Spongiform nodules are defined as nodules containing multiple small cysts <5 mm interspersed within solid tissue for nearly all the volume. EA is the preferred technique to use in case of cystic or predominantly cystic thyroid nodules, because it has fewer side effects and lower costs as compared to the other techniques [8]. The other techniques, particularly RFA, LA, and MWA are indicated for the treatment of spongiform, predominantly solid, or solid nodules [18,19].…”
Section: How To Choose a Specific Mitt Technique Over Another?mentioning
confidence: 99%
“…With EA, due to the aspiration of the fluid component, the nodule is immediately reduced in size after the treatment, with an immediate improvement of patients' symptoms. In the following time, the nodule continues to slightly reduce its volume, and generally it achieves a volume reduction of 60 to 80% at 6 months from treatment [8,21,22]. The technique efficacy of EA, which is defined as a volume reduction of at least 50% as compared to the initial nodule volume, is generally achieved in as much as 90% of cases.…”
Section: What Happens To the Nodule After Mitt?mentioning
confidence: 99%
See 1 more Smart Citation